Performance Analysis of Belief Propagation Polar Code Decoder. (October 2019) - Karthick, C; Vino, T; Babji, T; Naveen, P
Abstract: Attributable to their ability accomplishing execution and low encoding and interpreting intricacy, polar codes have gotten noteworthy consideration as of late. Successive cancellation decoding (SCD) and belief propagation decoding (BPD) are two mainstream approaches for disentangling polar codes. SCD, in spite of having less computational intricacy when contrasted and BPD, experiences long inertness because of the serial idea of the SC calculation. BPD, then again, is parallel in nature and is more alluring for low-dormancy applications. Nonetheless, because of the iterative idea of BPD, the required inertness and vitality dispersal increment straightly with the quantity of emphasis. In this paper, we propose a novel plan in light of sub-factor diagram solidifying to lessen the normal number addition the normal number of cycles required by BPD, which specifically converts into bring down inactivity and vitality dissemination. Besides, the equipment design for the proposed plot is created and contrasted and the best in class BPD executions for (1024, 512) polar codes.